2021
DOI: 10.14504/ajr.8.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Adsorption and Desorption of PHMB from Textile Surfaces

Abstract: Adsorption and desorption studies were done of polyhexamethylene biguanide (PHMB) onto two different types of textile fiber surfaces. Based on these studies and mathematical modelling, the rate constants were calculated. Two different experimental conditions were used to simulate laundering, namely wet-to-wet and dry-to-wet. The model PHMB surface concentrations showed that the model can be used to describe the adsorption kinetics on cotton and cotton-polyester blends with reasonable accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This was further confirmed by Bhaskara et al, who studied the kinetics of adsorption and desorption of PHMB on cotton fabrics using a mathematical model and found that nearly no PHMB was detached from the surface of fibres at low concentrations. 120 However, it was not the case when high concentrations of…”
Section: Textilesmentioning
confidence: 99%
See 1 more Smart Citation
“…This was further confirmed by Bhaskara et al, who studied the kinetics of adsorption and desorption of PHMB on cotton fabrics using a mathematical model and found that nearly no PHMB was detached from the surface of fibres at low concentrations. 120 However, it was not the case when high concentrations of…”
Section: Textilesmentioning
confidence: 99%
“…This was further confirmed by Bhaskara et al , who studied the kinetics of adsorption and desorption of PHMB on cotton fabrics using a mathematical model and found that nearly no PHMB was detached from the surface of fibres at low concentrations. 120 However, it was not the case when high concentrations of PHMB were involved. PHMB molecules formed multilayer stacking via layer-by-layer self-assembly at high concentrations, and the outer layer of PHMB molecules would be gradually dissociated from the stacking.…”
Section: Applicationsmentioning
confidence: 99%
“…This could be responsible for the strong a nity of PHMB molecules to cellulosic bres and the good durable properties of PHMB treated cellulosic fabrics in resistance to abrasion during wearing and household washing (Cao et al 2020;Chen-Yu et al 2007). Bhaskara et al (2021) studied the kinetics of adsorption and desorption of PHMB on cotton fabrics and concluded that nearly zero desorption PHMB was observed from the surface of cotton fabrics at low concentrations. The underlying reason may consist in both the electrostatic interaction and diffusion of PHMB molecules into the inner cores of cellulose bres.…”
Section: Introductionmentioning
confidence: 99%